Reduced Working Time as Political, Management and Control Instrument - Tessarini Junior, Geraldo; Saltorato, Patricia (Organizações & Sociedade, 2022)
Reduced working time is a topic widely discussed in organization studies, mainly its benefits. However, the literature does not deeply emphasize the power and control dynamics oftentimes observed in its implementation by organizations. The aim of the current article is to help fulfilling this gap by exploring different concepts about reduced working time in place in Brazilian federal educational institutions that have adopted the thirty-hour workweek as standard for their technical-administrative employees. A case study was carried out through observation, documental analysis and eighteen semi-structured interviews conducted with both workers subjected to shorter working hours and managers working under the conventional forty-hour week standard. Based on the results, despite its notable benefits for the work/life balance, the reduced working time has three interrelated purposes, namely: political, management, and control instrument. This research made it possible to reveal how management and control instruments can be incorporated to a policy focused on reduced working time, to highlight the complexity and controversy of power relation, as well as contributed to organization studies, based on rationalization about life and its temporal dimensions.